2013
DOI: 10.21101/cejph.a3840
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the July 2007 Heat Wave on Daily Mortality in Belgrade, Serbia

Abstract: Objective: Mortality has been shown to increase with heat waves. Serbia experienced the hottest heat wave in July 2007. In this study, we examined patterns of non-traumatic excess mortality in Belgrade during this event. Methods: The numbers of deaths observed during the 9-day heat wave were compared to those expected on the basis of mortality rates reported for the previous eight years and two following years. Excess mortality was analyzed by age, gender and cause of death. Results: There was a total of 167 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…A particularly extreme heat spell occurred in the second half of July 2007. During this episode, mortality increased by 38% in Belgrade (Bogdanović et al, 2013) and by 32.9% in Central Hungary (Páldy and Bobvos, 2010), and these values are much higher than in Slovakia (Tab. 1).…”
Section: Summer Heat In 2007mentioning
confidence: 95%
See 3 more Smart Citations
“…A particularly extreme heat spell occurred in the second half of July 2007. During this episode, mortality increased by 38% in Belgrade (Bogdanović et al, 2013) and by 32.9% in Central Hungary (Páldy and Bobvos, 2010), and these values are much higher than in Slovakia (Tab. 1).…”
Section: Summer Heat In 2007mentioning
confidence: 95%
“…No significant deficit in mortality, corresponding to mortality displacement, was recorded immediately after the July heat period in Moldova (Corobov et al, 2013), Serbia (Bogdanović et al, 2013), or in Hungary (Páldy and Bobvos, 2010). The authors of the cited Moldavian study, however, noticed markedly negative excess mortality in September 2007 and they stated that this was a reduction related to post-heat mortality displacement.…”
Section: Summer Heat In 2007mentioning
confidence: 96%
See 2 more Smart Citations
“…A huge amount of evidence has pointed to the relationship between daily variations in meteorological parameters and mortality [2]. The research conducted in Serbia has also shown heat-related mortality, especially among elderly females and Roma population [3,4]. On the other hand, the study which investigated the short-term effects of air pollution on cardiovascular mortality in the elderly in Nis, Serbia, did not show the association with the effects of the time trend, seasonal variations, a day of the week, temperature, relative humidity and barometric pressure [5].…”
Section: Introductionmentioning
confidence: 99%